Story maps e terremoti: Un nuovo strumento di informazione per la riduzione del rischio sismico (GEOmedia, 2015)
The increasing diffusion of story maps as a new communication and information channel allowed the Istituto Nazionale di Geofisica e Vulcanologia to experience this new technique in the field of seismic risk reduction. Starting from the experiences with the technology of ArcGIS On line for the development of applications on seismicity in Italy, we moved to the realization of some story maps to tell aspects of our territory related to seismic and tsunami risk. In particular, in the context of information campaigns "IO NON RISCHIO" promoted by the Dipartimento della Protezione Civile, interactive maps have been developed in support of the volunteers involved in information activities in the squares of the campaign. The story maps have been also used as a support for trainings, emergency management, in daily information on earthquakes together with the communication channels that INGV has recently developed for the information platform INGVterremoti (http://ingvterremoti.wordpress.com).(http://ingvterremoti.wordpress.com).